Scalable synthesis of n-type Mg3Sb2-xBix for thermoelectric applications. (March 2021) - Xu, C.; Liang, Z.; Shang, H.; Wang, D.; Wang, H.; Ding, F.; Mao, J.; Ren, Z.
Abstract: The highly efficient n-type Mg3 Sb2-x Bix thermoelectric materials hold great promise for application in power generation as well as refrigeration. Currently, n-type Mg3 Sb2-x Bix compounds with high zT s can be easily reproduced on a laboratory scale with ∼10 g per batch. However, scaling up the synthesis of Mg3 Sb2-x Bix with uniform high thermoelectric performance, which is critical for promoting this compound for practical applications, has yet to be achieved. Here we report a scalable preparation method based on Simoloyer ball-milling, which allows us to obtain over 1 kg Mg3.1 Sb1.5 Bi0.49 Te0.01 powder in a single batch. Subsequently, samples with different diameters (ranging from a half inch to two inches) were successfully prepared and their thermoelectric performance was found to be comparable. In addition, a two-inch sample was sectioned into several parts, and the thermoelectric properties of the separate parts are also similar, indicating the high uniformity of the prepared large-scale sample. Importantly, the single-leg Mg3.1 Sb1.5 Bi0.49 Te0.01 attains a high energy conversion efficiency of ∼12.9% under a temperature difference of ∼480 K at the hot-side temperature of 773 K. This study represents a step toward the practical application of Mg3 Sb2-x Bix for thermoelectric power generation. Graphical abstract: Image 1 Highlights: Scalable synthesis of n-type Mg3 Sb2-x Bix -based thermoelectrics. Capable of satisfying cheap mass production of Mg3 Sb2-x Bix -based thermoelectrics. Good thermoelectric performance, uniformity and high thermoelectric property of large-scale samples. A peak efficiency of ∼12.9% was achieved in a Mg3.1 Sb1.5 Bi0.49 Te0.01 single leg at the temperature difference of ∼480 K.